Neurotoxic reactive astrocytes drive neuronal death following retinal injury - Guttenplan, Kevin A. (Cell Rep, 2020)
Glaucoma is a neurodegenerative disease that features the death of retinal ganglion cells (RGCs) in the retina, often as a result of prolonged increases in intraocular pressure. We show that preventing the formation of neuroinflammatory reactive astrocytes prevents the death of RGCs normally seen in a mouse model of glaucoma. Further, we show that these spared RGCs are electrophysiologically functional and thus still have potential value for the function and regeneration of the retina. Finally, we demonstrate that the death of RGCs is dependent on a combination of both injury to the neurons as well as the presence of reactive astrocytes, suggesting a model that may explain why reactive astrocytes are toxic in some circumstances but not in others. Together, these findings highlight reactive astrocytes as drivers of RGC death in a chronic neurodegenerative disease of the eye.